Sleep Medicine A Comprehensive Guide to Its Development, Clinical Milestones, and Advances in Treatment - Chokroverty, Sudhansu; Billiard, Michel (Springer New York : Imprint: Springer, 2015)
This comprehensive volume provides a balanced and easily readable account of the rise of modern sleep medicine, its history and developmental milestones. Authored by an international group of experts, the remarkable progress and fascinating evolution from rudimentary concepts of the ancient prehistoric and early classical periods to our contemporary knowledge are covered in detail.  These examples and their relationship to modern therapies offer neurologists, psychiatrists, respiratory specialists, clinicians, researchers and those interested in sleep medicine an important perspective to the origins of current practice.